Modified Vaccinia Virus Ankara Encoding Influenza Virus Hemagglutinin Induces Heterosubtypic Immunity in Macaques - Florek, Nicholas W. (J Virol, 2014)
Current influenza virus vaccines primarily aim to induce neutralizing antibodies (NAbs). Modified vaccinia virus Ankara (MVA) is a safe and well-characterized vector for inducing both antibody and cellular immunity. We evaluated the immunogenicity and protective efficacy of MVA encoding influenza virus hemagglutinin (HA) and/or nucleoprotein (NP) in cynomolgus macaques. Animals were given 2 doses of MVA-based vaccines 4 weeks apart and were challenged with a 2009 pandemic H1N1 isolate (H1N1pdm) 8 weeks after the last vaccination. MVA-based vaccines encoding HA induced potent serum antibody responses against homologous H1 or H5 HAs but did not stimulate strong T cell responses prior to challenge. However, animals that received MVA encoding influenza virus HA and/or NP had high frequencies of virus-specific CD4(+) and CD8(+) T cell responses within the first 7 days of H1N1pdm infection, while animals vaccinated with MVA encoding irrelevant antigens did not. We detected little or no H1N1pdm replication in animals that received vaccines encoding H1 (homologous) HA, while a vaccine encoding NP from an H5N1 isolate afforded no protection. Surprisingly, H1N1pdm viral shedding was reduced in animals vaccinated with MVA encoding HA and NP from an H5N1 isolate. This reduced shedding was associated with cross-reactive antibodies capable of mediating antibody-dependent cellular cytotoxicity (ADCC) effector functions. Our results suggest that ADCC plays a role in cross-protective immunity against influenza. Vaccines optimized to stimulate cross-reactive antibodies with ADCC function may provide an important measure of protection against emerging influenza viruses when NAbs are ineffective. IMPORTANCE Current influenza vaccines are designed to elicit neutralizing antibodies (NAbs). Vaccine-induced NAbs typically are effective but highly specific for particular virus strains. Consequently, current vaccines are poorly suited for preventing the spread of newly emerging pandemic viruses. Therefore, we evaluated a vaccine strategy designed to induce both antibody and T cell responses, which may provide more broadly cross-protective immunity against influenza. Here, we show in a translational primate model that vaccination with a modified vaccinia virus Ankara encoding hemagglutinin from a heterosubtypic H5N1 virus was associated with reduced shedding of a pandemic H1N1 virus challenge, while vaccination with MVA encoding nucleoprotein, an internal viral protein, was not. Unexpectedly, this reduced shedding was associated with nonneutralizing antibodies that bound H1 hemagglutinin and activated natural killer cells. Therefore, antibody-dependent cellular cytotoxicity (ADCC) may play a role in cross-protective immunity to influenza virus. Vaccines that stimulate ADCC antibodies may enhance protection against pandemic influenza virus.